“Leaven in the Loaf”: The Wabash Center and Theological Education - Seymour, Jack L. (Teaching theology and religion, 2007)
Assessing the impact of Wabash Center programs on theological education, this article focuses on the vocation of the theological educator, particularly on the impact of theological teaching on faith and on the institutions, values, and practices that shape living. Five contributions of the Wabash Center are highlighted: (1) guiding seminary faculty in the practices of teaching, (2) enhancing the teaching preparation of doctoral students for theological education, (3) linking effective teaching to the development of seminary curricula, (4) enlarging the literature on teaching in theological education, and (5) nurturing the vocation of seminary educators.